2020
DOI: 10.1038/s41467-020-19284-w
|View full text |Cite
|
Sign up to set email alerts
|

Bulk valley transport and Berry curvature spreading at the edge of flat bands

Abstract: 2D materials based superlattices have emerged as a promising platform to modulate band structure and its symmetries. In particular, moiré periodicity in twisted graphene systems produces flat Chern bands. The recent observation of anomalous Hall effect (AHE) and orbital magnetism in twisted bilayer graphene has been associated with spontaneous symmetry breaking of such Chern bands. However, the valley Hall state as a precursor of AHE state, when time-reversal symmetry is still protected, has not been observed.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…For example, in Refs. (14)(15)(16)(17) non-local valley currents were reported in GBG, bilayer graphene-BN superlattice, and twisted double-bilayer graphene, respectively. However, nonlocal resistance fingerprints have also been predicted to originate from a spatially nonuniform gap profile (11,18), and recent scanning gate imaging experiments found that non-local transport signals in graphene can also arise because of charge accumulation at the edges, and therefore may not necessarily have a bulk valley Hall effect origin (19).…”
mentioning
confidence: 99%
“…For example, in Refs. (14)(15)(16)(17) non-local valley currents were reported in GBG, bilayer graphene-BN superlattice, and twisted double-bilayer graphene, respectively. However, nonlocal resistance fingerprints have also been predicted to originate from a spatially nonuniform gap profile (11,18), and recent scanning gate imaging experiments found that non-local transport signals in graphene can also arise because of charge accumulation at the edges, and therefore may not necessarily have a bulk valley Hall effect origin (19).…”
mentioning
confidence: 99%
“…More interestingly, the band dispersion of twisted moiré superlattices, in vicinity of the Fermi energy, are very sensitive to the twist angle (θ), and to the external electric field (∆) applied perpendicular to the 2D lattice plane. Both these parameters serve as experimental knobs for manipulating the electronic properties of moiré superlattices 35,37,50,51 . As an example, we show the evolution of the flat bands of the AB-AB stacked TDBG with the variation of the twist angle and externally applied vertical electric field in Fig.…”
Section: Moir é Flat Bands and Van Hove Singularitymentioning
confidence: 99%
“…In this section we demonstrate that the vertical electric field, the twist angle and electronic doping can also be used as knobs to modulate the interband and intraband plasmon dispersion in TDBG. Experimentally, electrostatic gating via a combination of the top and the back gate can be used to apply a vertical electric field and to change the electron doping in a controlled way 37,51 . The impact of the vertical electric field on the low energy plasmon modes of small angle TDBG is shown in Fig.…”
Section: Tunability Of the Plasmon Modes In Tdbgmentioning
confidence: 99%
“…Graphene, a one-atom-thick layer of carbon atoms arranged in a honeycomb lattice, is the prototype of a large class of two-dimensional materials such as transition metal dichalchogenoids 1 , van der Waals heterostructures 2 or twisted bilayers 3 and multilayers 4 that present striking properties such as topological, correlated or superconducting phases. It is the paradigm of Dirac fermions in condensed matter since its dispersion is described by the Dirac-Weyl equation in two dimensions 5,6 .…”
Section: Introductionmentioning
confidence: 99%